Spatiotemporal dynamics of soil organic carbon in desert region and its response to climate change: A case study of Heihe river - Yuqing Chen; Haiyang Xi; Wenju Cheng (Ecological Indicators)
Soil organic carbon (SOC) plays a vital role in regulating atmospheric CO2 levels. As global climate change intensifies, understanding the dynamics of the SOC pool becomes the key to assessing the potential for carbon sequestration in terrestrial ecosystems. However, the long-term response mechanisms of SOC density in desert regions to climate change remain unclear, increasing uncertainty in estimating the carbon sequestration potential of these ecosystems. This study aims to construct a comprehensive SOC database for the lower reaches of the Heihe River (HRL) and simulate the spatiotemporal distribution of SOC density within the 0 – 100 cm soil profile. The results indicate that the key indicators of different soil layers are not consistent for SOC density mapping in arid regions. Latitude (LAT), Elevation (ELE) and Normalized difference salinity index (NDSI) are particularly important in shallow soil layers (0–20 and 20–40 cm). Spatially, SOC density in the HRL is primarily distributed along river corridors, aligning closely with vegetation patterns. Additionally, SOC density shows a positive correlation with temperature and a negative correlation with precipitation. The period from the 2050 s to the 2060 s is a critical period for SOC changes in the HRL. Under the low-emission scenario (SSP 119), soil in the HRL shifted from being a carbon sink to a carbon source in the 2050 s. Under the medium-emission (SSP 245) and high-emission scenarios (SSP 585), soil remained a carbon sink overall but began transitioning around the 2060 s and 2050 s, respectively, before stabilizing. This study demonstrates significant carbon sequestration potential in arid region soils, highlighting their essential role in soil carbon storage that cannot be overlooked. The findings of this study provide data references and foundations for understanding the response of SOC in arid regions to climate change.